Proper microtubule structure is vital for timely progression through meiosis in fission yeast. - Akira Yamashita; Yoshihiro Fujita; Masayuki Yamamoto (PLoS ONE, 2013)
Cells of the fission yeast Schizosaccharomyces pombe normally reproduce by mitotic division in the haploid state. When subjected to nutrient starvation, two haploid cells fuse and undergo karyogamy, forming a diploid cell that initiates meiosis to form four haploid spores. Here, we show that deletion of the mal3 gene, which encodes a homolog of microtubule regulator EB1, produces aberrant asci carrying more than four spores. The mal3 deletion mutant cells have a disordered cytoplasmic microtubule structure during karyogamy and initiate meiosis before completion of karyogamy, resulting in twin haploid meiosis in the zygote. Treatment with anti-microtubule drugs mimics this phenotype. Mutants defective in karyogamy or mutants prone to initiate haploid meiosis exaggerate the phenotype of the mal3 deletion mutant. Our results indicate that proper microtubule structure is required for ordered progression through the meiotic cycle. Furthermore, the results of our study suggest that fission yeast do not monitor ploidy during meiosis.